Dynamic redox measurements with redox-sensitive GFP in plants by confocal laser scanning microscopy - Meyer, Andreas; Brach, Thorsten (Plant Signal Transduction, 2009)
Continuous control of metabolism and development is a key feature of life and is of particular importance under stress conditions. While under normal conditions most cellular compartments maintain a reducing environment, the cellular redox state can be influenced by external factors. Redox changes might in turn be employed as part of a signalling cascade leading to molecular responses to adverse situations. To enable dynamic measurements of the cellular redox poise in vivo, reduction-oxidation sensitive GFP (roGFP) can be expressed in plant cells and observed by confocal microscopy. When imaged by confocal microscopy this probe exhibits significant opposing shifts in the fluorescence intensities excited at 488 and 405 nm upon formation of an intramolecular disulfide bridge, which enables ratiometric analysis. The formation of the disulfide bridge is directly responsive to the redox state of the glutathione redox buffer within the subcellular compartment to which roGFP is targeted.
Gesehen am 15.05.2017